Environmentally driven escalation of host egg rejection decimates success of an avian brood parasite. (18th September 2020) - Eadie, John M; Lyon, Bruce E
Abstract: The black-headed duck ( Heteronetta atricapilla ) of South America is the only known avian obligate brood parasite with precocial offspring. In Argentina, it relies on two species of coots as primary hosts, which typically reject 35–65% of duck eggs. We show that environmentally driven increases in host egg rejection behavior lead to substantial reductions in the reproductive success of the brood parasite. Episodes of flooding and vegetation loss caused dramatic shifts in host egg-rejection behavior, resulting in rejection (85–95%) of almost all duck eggs. Coots respond to fluctuating water levels by building up their nest, raising their own eggs but leaving duck eggs behind. Coots can apparently recognize parasitic duck eggs, but large-scale rejection is triggered only when hosts must actively make a choice. We use a simple population model to illustrate the unique demographic challenges that black-headed ducks face with their parasitic lifestyle and to explore the potential impact of environmentally induced escalation of egg rejection. Using the best available estimates for key vital rates, we show that obligate parasitism may provide a demographically precarious existence for black-headed ducks, even under benign environmental conditions. Environmentally mediated increases in egg rejection rates by hosts could impact significantly the viability of this enigmatic species of brood parasitic duck. Our results demonstrate that egg rejection rates are not fixed properties of host populations or individuals but are strongly influenced by social and ecological factors. Shifts in these environmental drivers could have important and unforeseen demographic consequences for brood parasites. Abstract : Brood parasites depend on other species to raise their young, but parasitism is only a viable strategy if the hosts accept and raise some of the parasitic eggs. The two coot species that are the primary hosts of the black-headed duck of South America usually accept many duck eggs. However, during extreme environmental events like flooding and vegetation loss, coots reject virtually all duck eggs, causing the success of the parasitic ducks to plummet.